DEVELOPMENT OF PENCAK SILAT LEARNING MEDIA BASED ON MACROMEDIA FLASH 8 - Nurul Ihsan; Riko Valentino (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2019)
The purpose of this study is to develop an interactive multimedia on Pencak Silat materials using the application Macromedia Flash 8 for grade VIII and to find out the feasibility, practicality and effectiveness of learning media using Macromedia Flash 8. The development model used in this study is the development model of Borg and Gall. Applications based on the results of the validity test from the material experts obtained a value of 4.33 in the